The Carbon Concentrating Mechanism (CCM) of diatoms - Tan, Dexter Jun Xiang (2015)
Diatoms are an extremely successful major group of marine microalgae being responsible for about 20% of global primary production and thus global CO2-fixation, slowing down the intensification of climate-change. Despite their ecological significance, knowledge about these highly productive organisms is limited. Diatom’s efficient pyrenoid-dependent carbon-concentrating mechanism (CCM) saturates the CO2-fixing enzyme Ribulose-1,5-bisposphate-carboxylase/oxygenase (RuBisCo) with its substrate even under low CO2 conditions, keeping photosynthetic performance on a high level. The CCM-related low-CO2-inducible gene (LciB) was recently described in chlorophyta Chlamydomonas reinhardtii to be essential for growth at low CO2 conditions and to localise around the pyrenoid. However, the mechanism of CCM in the eukaryotic algae is unclear due to lack of functional analysis of proteins involved. In this study, diatom Phaeodactylum tricornutum’s carbonic anhydrase (PtCA1) and homologs of LciB (∆1-56PtLciB3, PtLciB4) were recombinantly expressed and purified from Escherichia coli to study the CCM in Phaeodactylum tricornutum. ∆1-56PtLciB3 and PtLciB4 were demonstrated to exist as oligomers in-vitro while PtCA1 was confirmed to be dimeric. Pull-down assays using PtLciB4 to bait for potential interaction partners in Phaeodactylum tricornutum have successfully revealed two unique pyrenoid-associated proteins (GapC1 and FbaC1) that are involved in carbon metabolism, indicating the possible involvement of PtLciB4 in CCM.